Two Interpretations of Nietzschean Concept of Nature: C. Alamariu and V. Lemm - Andrijauskas, Jokūbas (Problemos, 2024)
Nietzsche criticises religious interpretations of nature (Natur) and advocates the ‘naturalisation of humanity’. The various usages of the term ‘nature’ (Natur) have no clear, systematic definition in Nietzsche’s works, which is why the interpretations of this concept in Nietzsche’s studies are controversial. Two opposing perspectives emerge: Vanessa Lemm interprets nature as a Dionysian chaos which promotes an emancipatory rejection of the prevailing ideas, while Costin Alamariu sees it as an aristocratic phusis that fosters higher human types. This article argues that these seemingly contradictory views are compatible. Nietzsche uses the concept of nature as chaos to criticize anthropocentric views, while presenting the possibility of an understanding of nature detached from the human perspective. This paper analyses and criticizes Lemm’s illustration of this concept through sex differences. Finally, it is argued that Alamariu’s interpretation is in line with Nietzsche’s later positive ethico-political aspirations, often ignored in Nietzschean scholarship, concerning the development of higher human types.